A differential current-conveyor based buffer for high-bandwidth, low-signal applications - Alves, Luís Nero
This paper describes a novel differential buffer designed for high-bandwidth, low-power current transducers. This buffer uses modified class II current-conveyor cells, interconnected in such a way as to provide controlled impedance-matched differential inputs. This buffer is shown to provide a small current gain. Circuit simulations are presented and the circuit behaviour is analysed as a function of both input transducer characteristics and output loads. Noise considerations are also presented. This buffer is then applied to a wireless optical system. It increases overall system performance in both terms of gain and frequency response.